Insentif Pajak Bagi Dunia Bisnis Sebagai Upaya Pencegahan Kepailitan Pada Masa Pandemi Corona Virus Disease 2019 (Covid-19) - Yenny Yuniawaty Lunandi (Dialogia Iuridica, 2022)
The development of the national economy is supported by various business activities carried out in Indonesia. In business activities there is the potential to obtain economic benefits so that it cannot be separated from the obligation of entrepreneurs as business actors to pay taxes. Therefore, business and taxes are two things that are very crucial in the Indonesian economy to support public welfare. The Corona Virus Disease 2019 (Covid-19) pandemic has had a huge impact on the condition of the business world in Indonesia. With the policy of limiting community activities to control the spread of Corona Virus Disease 2019 (Covid-19), there are several affected business sectors experiencing financial distress. The financial distress can cause business actors whose business capital is loans from other parties, for example, banks cannot fulfill their obligations to pay debts that have matured and are threatened with bankruptcy. During the Corona Virus Disease (Covid-19) pandemic, there was an increase in bankruptcy cases which resulted in a slowdown in Indonesia's economic recovery. Government support for the business world in order to survive in the face of the Corona Virus Disease 2019 (Covid-19) pandemic by making policies in the field of taxation in the form of providing tax incentives to business people is an effort to prevent bankruptcy. Therefore, during the Corona Virus Disease 2019 (Covid-19) pandemic, the government needs to extend the period of providing tax incentives and expand sectors that are given tax incentives.